"Unity in Diversity": Neopluralism, the ESA Model, and the Rise of the General Federation of Women's Clubs. (3rd April 2021) - Chamberlain, Adam; Yanus, Alixandra B.
ABSTRACT: Most neopluralist studies consider how interest groups form in robust organizational environments, not during developmental periods such as the Progressive Era. In this article, we argue that neopluralist approaches, specifically the energy-stability-area (ESA) model, can provide insights on group formation in these contexts. Using the case of the General Federation of Women's Clubs (GFWC), we illustrate how one federated, voluntary association worked to increase its area, and by extension its energy, by diversifying its issue agenda. This led to internal density in the GFWC, further enabling it to engage members and clubs from both urban and rural areas. Thus, the ESA model serves as a theoretical framework for understanding how large-scale, federated voluntary associations sought to incorporate the density and diversity typical of the modern interest population into their own structure during this evolutionary period in American politics.